Pelagic larval polyclads that practice macrophagous carnivory. Issue 1 (18th February 2022) - von Dassow, George; Mendes, Cecili B.
Abstract: Among polyclad flatworms, many species are known to develop indirectly via long‐lived planktotrophic larvae, whereas the rest hatch as adult‐like juveniles. Such adult‐like hatchlings have been presumed to represent direct development. However, we report evidence that hatchling polyclads of several genera feed in the plankton on large prey. These ciliated swimmers, despite apparently lacking means to concentrate food or even detect it at a distance, subdue and consume fast‐moving active‐swimming plankters such as crustacean larvae and copepods, or molluscan veligers. We describe feeding events in captivity using videomicroscopy and identify several wild‐caught predatory pelagic polyclad larvae to genus or species level by DNA barcoding. Remarkably, one of these types is identified unambiguously with a species previously observed as Müller's larvae, which live as conventional planktotrophs on a diet inferred to consist of small phytoflagellates. Therefore, we conclude first that although so‐called direct‐developing polyclad flatworms may hatch with juvenile‐like morphology, at least some of these are functionally larvae. Second, these soft‐bodied ciliated larvae are neither lecithotrophs nor conventional planktotrophs feeding on unicellular algae, but pelagic predators; indeed, this may constitute the first demonstration that pelagic polyclads eat zooplankton. Third, some species of polyclad have at least a triphasic life cycle, in which a first larval stage lives in the plankton and feeds on primary producers, followed by a second larval stage that remains in the plankton to feed by macrophagous carnivory, before presumably settling to the benthos for adult life.